Dressing Out Percent And Some Carcass Characteristic of EL Gash Sheep - M. O. M, Omer; A.N, Ekhlas; O.M.A, Atif (Journal of Medical Biomedical and Applied Sciences, 2018)
This study was conducted to evaluate dressing out percent and carcass characteristic potentials of EL Gash sheep,under their natural habitat in Kassala town abattoir, Thirty , sheep 15 males and 15 females , were purchased formthe different local market of El Gash Area. Each sex was comprised of five groups , according to the age studied .live animals body weights were be taken before and after slaughtering .The evaluation of dressing out percent carcassyield characteristic were be taken. The slaughter data results significant difference between the two sexes . The resultindicated that dressing out percentage were 49.4% and 47.3% for the male and the female respectively with overallaverage of 48% . Slaughter at different ages showed significant differences in some parts of internal organs betweenthe two sexes. Alive weight, muscle, bone, trims, head, skin, rumen full, intestine full intestine empty, liver, heart, lungsreproductive organs and spleen were heavier in male than the female it might be due to the sex male hormone, butmesenteric fat, omentum fat, kidney knob canal fat [k.k.c.f], and fat were heavier in female than the males while muscle,bone, fat, trims, head, mesenteric fat, omentum fat, spleen and knob canal fat (k.k.c.f)were significant.